Utilization of Natural Zeolites as Cu (Ii) and Zn (Ii) Adsorbent - Dewi, Evi Mutiara; Suwardi, .; Suryaningtyas, Dyah Tjahyandari; Anwar, Syaiful (JOURNAL OF TROPICAL SOILS, 2016)
This research was aimed to determine the differences of physical and chemical characteristics from three natural zeolites from Tasikmalaya, Bayah and Lampung areas and to examine the characteristics of the natural zeolite adsorption capability to the micro-nutrients. The zeolite characterization analysis included some variables i.e. mineral types, morphologyand pH, CEC (Cation Exchange Capacity), BSP (Base Saturation Point), Cu and Zn content of zeolite. Analysis of natural zeolite adsorption characteristics were done by Batch System. Data interpretation were done by using the isothermal adsorption equation of Langmuir, Freundlich and Brunauer-Emmett-Teller (BET).The results showed that zeolite from Bayah and Tasikmalaya had a similiar morphology and it was categorized as mordenite types and platy structure, while zeolite from Lampung was a clinoptilolite type and tabular structure. The CEC of Tasikmalaya zeolite (137.58 cmol(-)kg-1) was higher than Bayah (96.75 cmol(-)kg-1) and Lampung (87.72 cmol(-)kg-1). Adsorption capability at the Langmuir equation of Cu by Bayah zeolite (47.619 mg g-1) was higher than Lampung (33.333 mgg-1) and Tasikmalaya (28.571 mg g-1). Effective adsorption of Zn by Bayah zeolite 19.417 mg g-1 was higher than Lampung (16.949 mg g-1) and Tasikmalaya (1.395 mg g-1).